Phe Keragaman Fenotipe Sapi Peranakan Ongole di Wilayah Sumber Bibit di Jawa Tengah (PHENOTYPE DIVERSITY OF ONGOLE GRADE CATTLE IN BREEDING AREA OF CENTRAL JAVA) - Sudaryanto, Agus Tri; Sutopo, Sutopo; Kurnianto, Edy (Jurnal Veteriner; Vol 19 No 4 (2018), 2019)
The eefforts to maintain and improve of the genetic quality of Ongole Grade (OG) in the breeding area of Central Java Province is low implemented, and it is feared that the quality of OG has decreased. One effort to maintain the superiority of genetic by identifying and studying the specific characters by female cattle. The objective of this study was to analyze the diversity of Ongole Grade (OG) grade body weight and morphology in three regencies of Central Java Province. Two hundred and twenty heads of OG cattle female belonging to farmer were used as a study object consisted of 75 heads, 75 heads and 70 heads of cattle come from Rembang Regency, Blora Regency and Kebumen Regency, respectively. The samples were determined by purposive sampling. Body measurements measured were shoulder height (SH), body length (BL), chest circumference (CC), pelvic height (PH), chest width (CW) and chest depth (CD). Body weight (BW) is calculated using a formula Schrool. Data were analyzed by using the Statistical Analysis System (SAS) ver. 6.12. The quantitative characteristics observed of female OG cattle in Rembang, Blora and Kebumen regencies showed diverse. The value of diversity is 3.2 - 11.2%. Body weight, body length, chest circumference and pelvic height showed significantly different (P<0.05). Average of body weight and body measurement of OG cattle in Kebumen are greater than Rembang and Blora regencies. Genetic relationships on the basic body weight and body measurements showed that female OG cattle in Rembang and Blora regencies had a closer relationship than that of to Kebumen regency.